Defining 'housing developer' and 'housing development' under Malaysian housing law - Md. Dahlan, Nuarrual Hilal; Kamarudin, Abdul Rani (Universiti Utara Malaysia Press, 2010)
The words ‘housing developer’ and ‘housing development’ have been defined in section 3 of the Housing Development (Control and Licensing) Act 1966 (‘the Act’). These statutory definitions have severally been discussed and examined by the courts in several cease law and it has been contended that the meanings of the definitions are too loose, enigmatic and vague. The certitude on the meaning of ‘housing developer’ and ‘housing development’ is a must for otherwise, it would be difficult for the Ministry of Housing and Local Government (MHLG) and as well as to the public to identify persons deemed to be ‘housing developers’ or carrying out ‘housing development".